Association of insulin receptor H1085H C>T, insulin receptor substrate 1 G972R and insulin receptor substrate 2 1057G/A polymorphisms with refractory temporal lobe epilepsy in Han Chinese. (February 2015) - Che, Fengyuan; Fu, Qingxi; Li, Xuesong; Gao, Naiyong; Qi, Faying; Sun, Zhiqing; Du, Yifeng; Li, Ming
Highlights: Association between insulin signaling gene polymorphism and refractory TLE was studied. INSR H1085H C>T, IRS1 G972R and IRS2 1057G/A were genotyped. INSR H1085H "T" allele may be a genetic risk factor for drug resistance in TLE. IRS2 "A" allele combined with INSR "T" allele increased the risk of drug resistance. Abstract: Purpose: Insulin/insulin receptor (INSR) signaling plays diverse roles in the central nervous system, including regulation of blood glucose, synaptic plasticity, dendritic growth, modulation of electrophysiological activity, proliferation of astrocytes and neuronal apoptosis. Interestingly, many of these and/or related processes represent biological mechanisms associated with temporal lobe epilepsy (TLE). Thus, insulin signaling may play a role in the development of TLE and its therapeutic responses. We hypothesized that functional polymorphisms in the insulin pathway genes INSR, insulin receptor substrate 1 (IRS1), and IRS2 may be associated with the therapeutic responses of TLE. Therefore, in this study we analyzed the association of three single nucleotide polymorphisms (SNPs) showing a risk for TLE drug resistance using a hospital-based case–control design. Method: Two hundred and one patients with refractory TLE and one hundred and seventy-five drug-responsive TLE patients were recruited for the study. Polymerase chain reaction–restriction fragment length polymorphism was used to detect the genotypes of INSR His1085His, IRS1 G972R and IRS2 1057G/A. Results: No significant differences between refractory and drug-responsive TLE patients were observed for the IRS1 G972R and IRS2 1057G/A polymorphisms ( P > 0.05), but a significant association was found for the INSR His1085His polymorphism for both genotypes ( P = 0.035) and alleles ( P = 0.011). IRS2 1057G/A combined with the INSR His1085His polymorphism increased the odds ratio of drug resistance in TLE ( P = 0.011, OR = 2.263, 95% CI: 1.208–4.239). Conclusion: These results suggest that a genetic variation in the insulin signaling pathway genes may affect the therapeutic response of TLE.